Pengaruh Profitabilitas, Transfer Pricing, dan Kepemilikan Asing Terhadap Tax Avoidance - Zarkasih, Effrida Nabillayanti; Maryati, Maryati (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
This study aims to obtain empirical evidence regarding the effect of profitability, transfer pricing, and foreign ownership on tax avoidance. This research is quantitative. The data source is in the form of secondary data obtained from the Financial Statements for 2016-2020. The population consisted of mining companies listed on the Indonesia Stock Exchange (IDX) using purposive sampling as the sampling technique and 10 companies were obtained as samples. Analysis of the research data is in the form of multiple linear regression analysis. The results of this study indicate that transfer pricing has a significant effect on tax avoidance, while profitability and foreign ownership have no significant effect on tax avoidance. Keywords: Profitability; Transfer Pricing; Foreign Ownership; Tax Avoidance